Analysis of Predicting the Exchange Rate of the IDR Against the US Dollar Using the Fuzzy Time Series Methods of Chen and Cheng - Aden, Aden; Oktaviani, Fani (Program Studi Matematika, Universitas Tadulako, 2024)
The rise and teh exchange rate of the IDR against the US dollar fall starting from 2021 to 2023 will have many impacts in the Indonesian economy both positive and negative impacts. The resulting impact affects the sustainability of the country's economic activities. To maintain the stability of the IDR exchange rate against the US dollar, it is necessary to do forecasting so that it can monitor the movement of the IDR exchange rate in the future. The puIDRose of this study is to find out how the results of the prediction of the IDR Exchange Rate (exchange) against the US Dollar with the Fuzzy Time Series Chen and Fuzzy Time Series Cheng methods and how the comparison of the implementation of the Fuzzy Time Series Chen and Fuzzy Time Series Cheng in predicting the IDR Exchange Rate (exchange) against US Dollar based on MAPE Value. The method used in this research is Chen and Cheng's Fuzzy Time Series. Forecasting results indicate the IDR exchange rate against the US dollar in June and July 2023 in the application of Chen's Fuzzy Time Series method of IDR 15,150.32 and the Fuzzy Time Series Cheng method of IDR 15,127.77. Then the data analysis shows that the MAPE results from the FTS Cheng method are better than the FTS Chen method with a MAPE percentage of 0.970%. The results of the acquisition of this percentage can be used as a reference for the government to weigh the economic policies that will be enacted in order to reduce the negative impacts arising from fluctuations in the IDR exchange rate.